A study on second language learning and motivation - Choong, Yvonne Foong Hiam; Rajab, Azizah; Habi, Hadina (2008)
This concept paper has presented some theories related to second language learning and motivation. A basic integrative motivation model in second language learning proposed by Gardner and Lambert (1982) has been introduced. Besides, pedagogical implications of Behaviourism, Cognitivism and Interactionism in second language learning are discussed. Based on the theories, a proper research will be done to find out the reasons and hindrances of learning a second language; and the motivational level in a language classroom will be studied as well (as shown in research questions).